Reliability of the ultrasonic pulse velocity for analysis and comparison of the compression strength of conventional concrete with addition of steel fiber and polypropylene (Gaceta Técnica, 2023)
The research aimed to evaluate the reliability of the ultrasonic pulse velocity method. The resistance of the concrete established by correlation curves by the ultrasonic pulse velocity and sclerometric index tests was estimated, developing simple and multiple correlation curves by the SonReb methodology. Using conventional concrete with the addition of 5% steel fibers and 0,21% polypropylene, with a mix design f´c = 21MPa. Seventy two 150 x 300mm concrete cylinders were prepared. On days 7, 14, 21, and 28, tests for compressive strength, sclerometric index, and ultrasonic pulse velocity were performed. In conclusion, the ultrasonic pulse velocity measurements revealed a good categorization of concrete quality as excellent and a strong dependency correlation. In general, the percentage of error presented by the analytical equations remains within +-10%
Keywords: ultrasonic pulse velocity for concrete; compressive strength of concrete; sclerometric index for concrete